2021
DOI: 10.7759/cureus.19879
|View full text |Cite
|
Sign up to set email alerts
|

Waning of Anti-spike Antibodies in AZD1222 (ChAdOx1) Vaccinated Healthcare Providers: A Prospective Longitudinal Study

Abstract: ConclusionWe found a substantial decline in antibody levels leading to seven cases of seroreversion in healthcare professionals who received the ChAdOx1 vaccine. History of prior COVID-19 was the only significant factor in antibody levels at six months. Seroreversion and breakthrough infection warrant further research into the optimal timing and potential benefits of booster doses of the AZD1222 (ChAdOx1) COVID-19 vaccine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 26 publications
(45 reference statements)
2
24
0
1
Order By: Relevance
“…This difference in antibody levels may be due, in addition to geographical and racial variations, to the small number of participants in our study compared to the Indian study (41 vs. 308, respectively). In a study conducted by Mishra and his collaborators on 122 health workers who received a full dose of ChAdOx1 nCoV-19 vaccine, a high seroprevalence rate (94.26%) similar to the prevalence obtained in our study (90%, 37/41) was reported [ 51 ]. A study conducted on 203 BBIBP-CorV vaccine recipients showed a high seroprevalence rate of 95.07% three months post-vaccination [ 52 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This difference in antibody levels may be due, in addition to geographical and racial variations, to the small number of participants in our study compared to the Indian study (41 vs. 308, respectively). In a study conducted by Mishra and his collaborators on 122 health workers who received a full dose of ChAdOx1 nCoV-19 vaccine, a high seroprevalence rate (94.26%) similar to the prevalence obtained in our study (90%, 37/41) was reported [ 51 ]. A study conducted on 203 BBIBP-CorV vaccine recipients showed a high seroprevalence rate of 95.07% three months post-vaccination [ 52 ].…”
Section: Discussionsupporting
confidence: 86%
“…Various studies that were conducted in order to understand the kinetics and durability of antibodies induced after vaccination (ChAdOx1 nCoV-19 and BBIBP-CorV) showed that the immune response persists for up to three to four months, but begins to decline significantly over time [ 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. A study of 122 healthy individuals vaccinated with BNT162b2, where the authors used the same test used in this study to determine the level of antibodies six months after the second dose, reported a decrease in the level of antibodies, but this level was still very high compared to our study (1383 AU/mL).…”
Section: Discussionmentioning
confidence: 99%
“…Our finding is in contrary to the only other longitudinal study of Covaxin in Indian HCWs that found a 4-fold decrease in median anti-spike antibody titer at 6-month whilst Covishield recipient had only 2-fold decline despite a significantly higher median antibody titer with Covishield at all time points vs. Covaxin [ 11 ]. As mentioned earlier, other Indian study reported a 72% decay rate in antibody titre at 6-month in Covishield recipient [ 10 ]. The reason for this discrepancy of slow decay of antibody with Covaxin in our study is not exactly known and needs to be studied, however, however at least one comparative Indian study found Covaxin generating better cell-mediated immunity compared to Covishield whilst Covishield was more effective in inducing humoral immunity compared to Covaxin [ 18 ].…”
Section: Discussionmentioning
confidence: 77%
“…In a cross-sectional longitudinal study of 552 participants from England and Wales there was a significant decline in anti-spike antibody both with ChAdOx1 (five-fold decline) and BNT162b2 (two-fold decline) at 10-weeks after two complete doses of either vaccine [ 9 ]. From the Indian vaccine study standpoint, a prospective longitudinal study from India involving 122 HCWs found a substantial decline in levels of anti-spike antibody (S1 subunit) at 6-month compared to the peak values (one month) after the second dose of the Covishield vaccine, suggesting a sharper decay rate of 72% [ 10 ]. Another longitudinal cohort study involving 533 HCWs that compared humoral response in both Covishield and Covaxin recipients found a 2- and 4-fold decrease in anti-spike antibody titer respectively, at 6 months, when measured as median value (95% IQR) [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In those who previously had COVID-19, a single dose induced very high levels of ACE2-blocking antibodies and antibodies to RBDs [44]. Mishra et al [45] analyzed the kinetics of the change in antibody levels for this vaccine and showed a significant decrease in antibody levels 6 months after injection. In their research, as in ours, the history of prior SARS-CoV-2 infection was the only significant factor in antibody levels for ChAdOx1-2019.…”
Section: Discussionmentioning
confidence: 99%